Hubungan Irrational Belief dengan Self Acceptance Siswa Yang Memiliki Hasil Belajar Rendah - Amirah, Nadiratul; Taufik, Taufik (Current Issues in Counseling, 2023)
This research is motivated by the large number of students who obtain low learning outcomes. The low learning outcomes are influenced by a number of factors, including internal factors in the form of self-acceptance. Students who have low learning outcomes tend to be less able to accept themselves with their shortcomings. The low self-acceptance is caused by many who have irrational beliefs in a person. This study aims to describe the conditions of irrational belief and self-acceptance in students who have low learning outcomes and examine the relationship between irrational belief and self-acceptance in students who have low learning outcomes. This research is a quantitative research using a descriptive correlational approach. The population in this study were students of SMP Negeri 15 Padang who had low learning outcomes. The sample of this research was 85 students using random sampling technique. The instrument used in this study was a Likert scale model questionnaire. Data were analyzed using the Product Moment Correlation technique. The findings of this study are (1) as many as 64% of students with low learning outcomes have moderate irrational beliefs, (2) as many as 68% of students with low learning outcomes in moderate self-acceptance conditions and (3) there is a relationship between irrational beliefs and self-acceptance in students with low learning outcomes with a correlation coefficient of 0.289 which is classified as weak.